If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (x + -4)(x + 5) = 0 Reorder the terms: (-4 + x)(x + 5) = 0 Reorder the terms: (-4 + x)(5 + x) = 0 Multiply (-4 + x) * (5 + x) (-4(5 + x) + x(5 + x)) = 0 ((5 * -4 + x * -4) + x(5 + x)) = 0 ((-20 + -4x) + x(5 + x)) = 0 (-20 + -4x + (5 * x + x * x)) = 0 (-20 + -4x + (5x + x2)) = 0 Combine like terms: -4x + 5x = 1x (-20 + 1x + x2) = 0 Solving -20 + 1x + x2 = 0 Solving for variable 'x'. Factor a trinomial. (-5 + -1x)(4 + -1x) = 0Subproblem 1
Set the factor '(-5 + -1x)' equal to zero and attempt to solve: Simplifying -5 + -1x = 0 Solving -5 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '5' to each side of the equation. -5 + 5 + -1x = 0 + 5 Combine like terms: -5 + 5 = 0 0 + -1x = 0 + 5 -1x = 0 + 5 Combine like terms: 0 + 5 = 5 -1x = 5 Divide each side by '-1'. x = -5 Simplifying x = -5Subproblem 2
Set the factor '(4 + -1x)' equal to zero and attempt to solve: Simplifying 4 + -1x = 0 Solving 4 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '-4' to each side of the equation. 4 + -4 + -1x = 0 + -4 Combine like terms: 4 + -4 = 0 0 + -1x = 0 + -4 -1x = 0 + -4 Combine like terms: 0 + -4 = -4 -1x = -4 Divide each side by '-1'. x = 4 Simplifying x = 4Solution
x = {-5, 4}
| 1.1=4y+16.7 | | .40*55=x | | 5(x-3)=8-3x | | 6x^3-5x^2-4x+3= | | 6x^3-5x^2-4x+3byx-1= | | x^2-11x-9=0 | | x^2-4x+2=-2 | | 7x-3=12+2x | | 1(1x+12)= | | d-15=3d-3 | | 48-7d=-8+d | | 18d+1=17d+6 | | 16-d=d+4 | | d-4=2d-14 | | 44-3c=11 | | 4(c-2)=0 | | 2c+6=12 | | 6b=-2 | | 15-b=20 | | -b+4=1 | | b+17=3 | | a+7=13 | | 7(h-5)=14 | | (4x-11)-(x-12)= | | 3A*6A=14 | | 3(c+1)=-12 | | 5(d-3)=40 | | 3A*6A= | | 4x+x-2=3x | | 5x+7=x+31 | | 4w+18=54 | | 3t-5=28 |